STRATEGI KOMUNIKASI DAKWAH TAREKAT NAQSYABANDIYAH DALAM PENDAMPINGAN SECARA SPRITUAL TERHADAP KORBAN PENYALAHGUNAAN NARKOBA DI TANJUNGBALAI - Kholik, Abdul; Pahlawan Hasibuan, Muhammad Rizki Nanda (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2025)
In responding to the problem of drug abuse, the Naqsyabandiyah Order is here to provide an alternative method to rehabilitate victims of drug abuse using the amaliah of the Naqsyabandiyah Order such as dhikr and wirid, talqin, khataman and everything that is intended to bring oneself closer to Allah SWT. This study aims to find out about how to use the Naqsyabandiyah Order method for drug abuse. This study uses a qualitative approach with a descriptive type. Data were taken through in-depth interviews and observations as well as documentation. Data analysis was carried out using the Milles Huberman model. The results of this study are the Naqsyabandiyah Order's da'wah communication strategy applied to victims of drug abuse by means of an intensive persuasive communication process to build a sense of comfort and security in each client who is a victim of drug abuse which can be a starting point in eliminating anxiety and building hope for victims of drug abuse to recover. Communication techniques used for victims of drug abuse include reflective communication techniques and assertive communication techniques.